Comparative Study on Gene Expression for Detecting Diseases Using Optimized Algorithm. (2nd January 2017) - Sumitha, J.; Devi, T.; Ravi, D.
ABSTRACT: The main objective is to detect the disease-causing gene from microarray data and predict the results from the gene expression value. Many computer-assisted algorithms developed to predict the characteristic of a gene is done using machine learning and other bio-inspired algorithms. In this paper, seven works are proposed and compared to estimate the efficiency. The Support Vector Machine (SVM) optimized neuro-expert algorithm is developed to optimize these predictive results of both machine learning and bio-inspired algorithms and proven its effectiveness and efficiency in detecting the disease-causing gene than ever before.